Bridging Knowledge and Readiness: The Relationship Between Menstrual Awareness and Menarche Preparedness Among Elementary School Girls in Badung, Bali - Hesteria Friska Armynia Subratha; Nabila Amelia Hanisyah Putri; Nis'atul Khoiroh; Made Suadnyani Pasek; Ida Ayu Diah Purnama Sari; Luh Ita Mahendrayani (WMJ (Warmadewa Medical Journal), 2025)
Menarche represents a key developmental transition in early adolescence, making it essential to understand how menstrual knowledge shapes girls’ preparedness for this event. This cross-sectional study examined the relationship between menstrual knowledge and menarche preparedness among elementary school girls in Badung, Bali. A total of 150 students in grades 4–6 from five public schools, purposively selected due to low literacy and numeracy indicators, participated in the study. Data were collected using validated, self-administered questionnaires assessing menstrual knowledge and preparedness. Chi-square analysis with Odds Ratio (OR) estimation was employed. Most participants demonstrated good menstrual knowledge (60.0%) and were categorized as prepared for menarche (63.3%). A significant association was observed between menstrual knowledge and preparedness (p < 0.001; OR = 5.50; 95% CI: 2.65–11.41), indicating that students with higher knowledge levels were substantially more likely to be well prepared. Parental support and exposure to information from schools or health professionals also appeared to contribute to improved preparedness. These findings underscore the importance of strengthening school-based reproductive health education, complemented by active family engagement and culturally appropriate learning materials, to enhance early menarche readiness among young girls.